2022
DOI: 10.3390/app12126024
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intersection Management Based on an Adaptive Fuzzy-Logic Traffic Signal

Abstract: Traffic signals may generate bottlenecks due to an unfair timing balance. Facing this problem, adaptive traffic signal controllers have been proposed to compute the phase durations according to conditions monitored from on-road sensors. However, high hardware requirements, as well as complex setups, make the majority of these approaches infeasible for most cities. This paper proposes an adaptive traffic signal fuzzy-logic controller which uses the flow rate, retrieved from simple traffic counters, as a unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…As the field progressed, the literature expanded its horizons, illustrating a myriad of practical applications spanning industries. In the realm of industrial automation, fuzzy controllers found homes in an array of settings, from optimizing power systems [31][32][33] and managing traffic flow [34][35][36] to orchestrating robotic operations [37][38][39]. These realworld implementations demonstrated the adaptability and effectiveness of fuzzy logic in scenarios where traditional mathematical models struggled due to system complexity and unpredictable variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the field progressed, the literature expanded its horizons, illustrating a myriad of practical applications spanning industries. In the realm of industrial automation, fuzzy controllers found homes in an array of settings, from optimizing power systems [31][32][33] and managing traffic flow [34][35][36] to orchestrating robotic operations [37][38][39]. These realworld implementations demonstrated the adaptability and effectiveness of fuzzy logic in scenarios where traditional mathematical models struggled due to system complexity and unpredictable variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A phase diagram illustrates all movements being made in a given phase within a single block of the diagram. A ring diagram illustrates which movements are controlled by each "ring" on a signal controller [43].…”
Section: Fixed Time Traffic Signal Control (Ftsc)mentioning
confidence: 99%
“…For imagelike state representations, states contain rich raw information and can extract traffic features from it with the help of convolutional neural networks. However, such states may be challenging to implement in the real world because of computational costs, communication latencies, and stringent detector requirements [34][35][36][37]. For feature-based state representations, researchers and experts choose suitable variables for the feature vectors based on their experience.…”
Section: Statementioning
confidence: 99%